Deep as the sky, red as the sea : a novel - Chang-Eppig, Rita (Bloomsbury Publishing, 2023)
"When Shek Yeung sees a Portuguese sailor slay her husband, a feared pirate, she knows she must act swiftly or die. Instead of mourning, Shek Yeung launches a new plan: immediately marrying her husband's second-in-command, and agreeing to bear him a son and heir, in order to retain power over her half of the fleet. But as Shek Yeung vies for control over the army she knows she was born to lead, larger threats loom. The Chinese Emperor has charged a brutal, crafty nobleman with ridding the South China Seas of pirates, and the Europeans--tired of losing ships, men, and money to Shek Yeung's alliance--have new plans for the area. Even worse, Shek Yeung's cutthroat retributions create problems all their own. As Shek Yeung navigates new motherhood and the crises of leadership, she must decide how long she is willing to fight, and at what price, or risk losing her fleet, her new family, and even her life"--